2008
DOI: 10.1097/fbp.0b013e3282f3cf70
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naltrexone, duloxetine, and a corticotropin-releasing factor type 1 receptor antagonist on binge-like alcohol drinking in rats

Abstract: A 'binge' is defined by National Institute on Alcohol Abuse and Alcoholism as an excessive pattern of alcohol drinking that produces blood-alcohol levels (BALs) greater than 0.08 g% within a 2-h period and may or may not be associated with dependence. The purpose of this investigation was to explore the effects of several neuropharmacological agents in an animal model in which outbred rats voluntarily and orally self-administer pharmacologically meaningful alcohol doses that produce BALs ≥ 0.08 g% in daily lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
77
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 65 publications
12
77
2
Order By: Relevance
“…Among non-human vertebrates commonly involved in alcohol research are primates [90,91,148] , pigs [104,120] , dogs [114,121] , mice [70,72,74,86,89,96,109,118,119,141] , rats [88,94,108,149,150] and rabbits [132] . The rodent AAA models (mice and rats) are used most frequently due to their relatively well-defined genetic background and the availability of diverse genetic traits, including those coding for high or low alcohol consumption [88,89,96,109] .…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among non-human vertebrates commonly involved in alcohol research are primates [90,91,148] , pigs [104,120] , dogs [114,121] , mice [70,72,74,86,89,96,109,118,119,141] , rats [88,94,108,149,150] and rabbits [132] . The rodent AAA models (mice and rats) are used most frequently due to their relatively well-defined genetic background and the availability of diverse genetic traits, including those coding for high or low alcohol consumption [88,89,96,109] .…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%
“…The rodent AAA models (mice and rats) are used most frequently due to their relatively well-defined genetic background and the availability of diverse genetic traits, including those coding for high or low alcohol consumption [88,89,96,109] . Most non-human AAA models currently in use [93,95] examine relative oral self-administration from a bottle containing alcohol versus one [86,94,108] or multiple bottles [119] containing water (preference drinking) or administration of alcohol against the will, either by physiological (by mouth using gavage)…”
Section: Non-human Aaa Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alcohol-preferring rat (P-rat) has been effectively used as a small animal model to study binge drinking (Li et al, 1987). In the P-rat, naltrexone (Biggs and Myers, 1998;Gilpin et al, 2008;Ji et al, 2008) and other opioids (Weiss et al, 1990) have been shown to be effective in decreasing alcohol self-administration. Nalmefene (Scheme 1), the 6-methylene analog of naltrexone, is a more potent k-opioid antagonist than naltrexone and is an effective antagonist of alcohol self-administration in outbred and P-rats (June et al, 1998(June et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%